Implementation of EMR on the Completeness of Inpatient Medical Records at Oto Iskandar Di Nata General Hospital - Setiatin, Sali; Sari, Mutiara Cinta (Greenation Publisher & Yayasan Global Research National, 2025)
As health service providers, hospitals have been required to implement an electronic medical record (EMR) system. The goal of implementing an EMR is to improve the accuracy, efficiency, and security of patient medical data. Good medical records are also an indicator of hospital quality, supporting the accreditation process and service efficiency. The author's analysis is motivated by the need to understand the impact of EMR implementation at Oto Iskandar Di Nata General Hospital on the completeness of medical record data. The research method is a descriptive, quantitative analysis with a checklist form as the research instrument. The results showed that the highest percentage of completeness was in the important part of the report with an overall percentage of 89%, while the lowest percentage was in the author authentication section with an overall percentage of 66%. One of the reasons for incompleteness was due to system limitations. In conclusion, although the EMR system has begun to be implemented, the level of data completeness still does not meet the standards set by the Ministry of Health Regulation.